Phytosanitary challenges and solutions for roots and tubers in the tropics - Andrade-Piedra, Jorge L.; Sharma, Kalpana; Kroschel, Jürgen; Ogero, Kwame; Kreuze, Jan; Legg, James P.; Kumar, P. Lava; Spielman, David J.; Navarrete, Israel; Perez, Willmer; Atieno, Elly; Garrett, Karen A. (Annual Reviews, 2025)
Vegetatively propagated crops such as cassava, potato, sweetpotato, and yam, or roots and tubers (RTs), play a major role in food security in low- and middle-income countries, yet phytosanitary issues in the tropics lead to substantial yield and quality losses. Challenges to production include institutional limitations that prevent effective responses and potential buildup of pathogens during clonal propagation. Addressing these challenges in a climate change context and diverse sociocultural environments requires a multifaceted approach, including improving access and availability to clean seed by strengthening seed systems; breeding for host resistance and disseminating resistant varieties; strengthening on-farm seed management; and designing effective policies and regulations to deal with seedborne diseases. Vital cross-cutting activities that can help to tackle the phytosanitary challenges of RTs include capacity strengthening, research on emergent pathogens, and improving regional cooperation and harmonization of phytosanitary standards to manage transboundary seed movement.